Professional Development of Professors of Medicine for Improving the Teaching-Learning Process - Pedro Miguel Milián Vázquez; Lidia Vázquez Montero; Omeris Mesa González; Magdalena O. Albelo Amor; Helvia M. Reyes Cabrera; José Catalino Bermúdez Martínez (Medisur)
Improvement of the teaching-learning process of medical sciences requires the professional development of professors. This article aims to reflect on the professional development process of professors of medicine in Cuba. The characteristics of professional development in the context of medical sciences in the country (objectives, contents, methodological strategies, modalities, and forms of professional development) are described. The particular case of the professional development of professors of medicine is referred to and the lack of options is shown. The relation between this problem and the improvement of the teaching-learning process of a particular discipline, such as Pharmacology, is addressed. Finally, the conditions that should guide the process of professional development towards this improvement are provided.